Creative Self-Efficacy: Its Potential Antecedents and Relationship to Creative Performance - Tierney, Pamela; Farmer, Steven M. (Academy of Management Journal, 2002)
Using data from two different firms, this study tested a new construct, creative self-efficacy, tapping employees' belief) that they can be creative in their work roles. Results support the discriminant validity of the construct and indicate that job tenure, job self-efficacy, supervisor behavior, and job complexity contribute to creative efficacy beliefs. Creative self-efficacy also predicted creative performance beyond the predictive effects of job self-efficacy. Differences in results between white-collar and blue-collar samples suggest considerations for both theory and practice.